PERANCANGAN PROTOTYPE INTERNET OF THINGS (IOT) SISTEM MONITORING INDOOR AIR QUALITY - Hasan, Nia Yuniarti; Prijanto, Teguh Budi; Kahar, Kahar (Poltekkes Kemenkes Bandung, 2024)
The health of household occupants can be significantly influenced by indoor air quality, a crucial factor. Currently, real-time measurement of indoor air quality is not feasible. Consequently, there is a need to create sensor technology capable of reading air quality concentration data and transmitting information via internet connectivity. This sensor technology is part of the broader Internet of Things (IoT) ecosystem. This study aimed to create an IoT prototype for real-time measurement of SO2, NO2, PM10, and PM2.5 gas concentrations in residential settings. The research employs a Research and Development (R&D) methodology, with real-time sample data collection and descriptive analysis. The prototype's measurements revealed concentrations (g/m3) of SO2 (0.0100-0.1011), NO2 (0.0005-0.9352), PM10 (51-128), and PM2.5 (43-121). Over 24 hour period, average measurements indicated that SO2 concentration met the standard (0.1 g/m3), while NO2 exceeded the limit (0.04 g/m3), as did PM10 (70 g/m3) and PM2.5 (35 g/m3). This prototype can measure indoor air quality parameters such as SO2, NO2, PM10, and PM2.5, with results viewable on both an LCD and the Blynk Android application.